Recent advances in semi-transparent polymer and perovskite solar cells for power generating window applications - Xue, Qifan; Xia, Ruoxi; Brabec, Christoph J; Yip, Hin-Lap (Energy & environmental science, 2018)
Semi-transparent photovoltaic (ST-PV) technologies can be applied to replace facades and roofs in conventional buildings and coatings on vehicles to produce energy from sunlight. Current ST-PV technology is Si-based, but although Si achieves adequate efficiencies, it compromises on aesthetic appeal; its color is intrinsically difficult to tune. However, this presents an opportunity for semi-transparent polymer and perovskite-based PVs, the optical properties of which can be modulated easily by tuning their material compositions. In this review article, we summarize recent progress made in the material selection, optical engineering and device architecture design for high-performance, semi-transparent polymer and perovskite solar cells and discuss challenges for the commercialization of these semi-transparent solar cells for power-generating applications in windows. Semi-transparent photovoltaic (ST-PV) technologies can be applied to replace facades and roofs in conventional buildings and coatings on vehicles to produce energy from sunlight.